The impact of Islam on the concept of government of the sultanate of Malacca during the 15th century - Mamat, Ismail (Penerbit UTM Press, 2018)
This article attempts to look at the impact of Islamization process on the Sultanate of Malacca during the 15th century. Islam has offered civilizational life for the Malays. Malacca grew from an unknown place during the pre-Islamic period to become one of the well-known centres of Islamic religion and culture in the region. Islam has changed the status of Malacca after reducing its pre-Islamic customs and ways of life. The importance of the Malay Sultanate of Malacca has been well-documented and much has been written about it by many authors either by Malaysians such as Buyong Adi1, Kernal Singh Sandhu, Mohd Jamil Mukmin, Mohd Taib Osman, Muhammad Yusoff Hashim, Abu Hassan Sham, Khoo Kay Kim, and Joginder Singh Jessy, and Zubir Usman, or by the non-Malaysians including R. O. Winstedt, R. J. Wilkinson, Walter William Skeat, C. O. Blagden, Paul Wheatley, D. G. Hall, F. J. Moorhead, J. Bantin and R. Roolvink, J. Kennedy, John Bastin, Liang Liji, M. B. Hooker, Nicholas Tarling, Paul Wheatley, Sarnia Hayes Hoyt, T. W. Arnold, W. P. Groeneveldt, Christoper H. Wake, P. E. de Josselin de Jong and H. L. A van Wijk, Robert W. McRoberts, and Wang Gangwu. They wrote on various genres of literature and culture of the Malays as well as the history of the Sultanate. However, some of them especially the orientalists, because of their adoption of various Western social theories, this application of such theory to the sultanate or the Malay society yield untenable results. We shall argue some of whom tend to regard Islam as unimportant in shaping the Malay worldview, society and identity. This article will emphasize the civilizational significance of the Islamic impact by looking at the system of political authority and the concept of government of the Sultanate.